2015
DOI: 10.1590/1807-1929/agriambi.v19n6p521-526
|View full text |Cite
|
Sign up to set email alerts
|

Medições e modelagem da pegada hídrica da cana-de-açúcar cultivada no Estado da Paraíba

Abstract: R E S U M OO conceito de pegada hídrica tem tido bastante interesse atualmente haja vista que a água doce é um recurso global utilizado em todos os ramos de atividades e pode ser fundamental para ajudar a compreender como as atividades e os produtos estão relacionados com a escassez de água. O objetivo deste estudo é comparar as medições da pegada hídrica da cana-de-açúcar derivadas pelo método tradicional utilizado na sua estimativa usando o balanço hídrico completo no solo em condições de campo. O experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Estimated water footprints include uncertainties in all studies. Silva et al [40] compared the sugarcane water footprint estimates derived from modeling with the CropWat model and those obtained from field studies and found that Mekonnen and Hoekstra [41] significantly overestimated the water footprints of sugarcane grown in rain-fed systems in Brazil.…”
Section: Discussionmentioning
confidence: 99%
“…Estimated water footprints include uncertainties in all studies. Silva et al [40] compared the sugarcane water footprint estimates derived from modeling with the CropWat model and those obtained from field studies and found that Mekonnen and Hoekstra [41] significantly overestimated the water footprints of sugarcane grown in rain-fed systems in Brazil.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of the WF for water basins located in São Paulo, Scarpare et al (2015) found the blue, green and grey WFs of sugarcane to be 38, 145 and 18 m³ t -1 , respectively. Silva et al (2015), meanwhile, yielded results of 107.39, 119.56 and 9.00 m³ t -1 , respectively, for the blue, green and grey WFs of sugarcane grown in the state of Paraíba using the CropWat model. These latter authors also found that in treatment with irrigation at 100% evapotranspiration, the blue WF (measured at 97.71 m³ t -1 ) was higher than the green WF (50.24 m³ t -1 ).…”
Section: Water Footprint Of Sugarcanementioning
confidence: 98%
“…Mekonnen and Hoekstra (2011a;2011b; estimated the grey water footprint of approximately 287.1 m 3 t -1 for the wheat culture. Silva et al, (2015) reported the value of 20.77 m 3 ha -1 for GWF of sugar cane in a dry-farming cultivation system. These results were well lower than those we found in our study.…”
Section: Grey Water Footprint For Onionmentioning
confidence: 99%
“…In this context, the grey water footprint is characterized as the volume of freshwater required to dilute the load of pollutants, taking into consideration the natural concentrations and in the environmental standards in place (Hoekstra and Chapagain, 2007). Hoekstra (2009) and Silva et al (2015) reported that pollution of the waters can be expressed in terms of the volume of water needed to dilute pollutants so that they become ineffective.…”
Section: Introductionmentioning
confidence: 99%